Public finance - Rosen, Harvey S. (Irwin publications in economics, 2014)
Introducing ... Public Finance, 10th Global Edition, by Harvey S. Rosen and Ted Gayer Rosen and Gayer's Public Finance provides the economic tools necessary to analyze government expenditure and tax policies and, along the way, takes students to the frontiers of current research and policy. While the information presented is cutting edge and reflects the work of economists currently active in the field, the approach